(untitled) (Modern education and development, 2025)
Facial mimetic muscles are responsible for the wide range of expressions humans use to communicate emotions nonverbally. These muscles differ from other skeletal muscles in that they insert directly into the skin rather than bone, allowing precise movements of the face. This article reviews the anatomy of facial mimetic muscles and explores the neural control systems that govern their activity, focusing on the facial nerve (cranial nerve VII) and its central regulatory pathways. Understanding these mechanisms is crucial for clinical management of facial paralysis and related disorders.